2015
DOI: 10.1016/j.jher.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Incompressible SPH simulation of open channel flow over smooth bed

Abstract: The Smoothed Particle Hydrodynamics (SPH) modelling techniques are used in a variety of coastal hydrodynamic applications, but only limited works have been documented in the open channel flows. In this paper, we use the incompressible SPH model combined with an improved inflow boundary scheme to investigate the open channel flows in a laboratory scale. The inflow and outflow boundary conditions are treated by generating and removing the fluid particles at the channel end. The proposed ISPH model has been appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Two uniform laminar flow test cases of open channels [18] were simulated. The length of the numerical channel was 1.0 m. The slope was 0.04% for case 1 and 0.1% for case 2.…”
Section: Open Channel Flowmentioning
confidence: 99%
“…Two uniform laminar flow test cases of open channels [18] were simulated. The length of the numerical channel was 1.0 m. The slope was 0.04% for case 1 and 0.1% for case 2.…”
Section: Open Channel Flowmentioning
confidence: 99%
“…Meister et al [2014] performed the same numerical technique and the analytical solution of the main velocity and the corresponding pressure distribution were initially imposed. Moreover, Tan et al [2015] performed an incompressible SPH (ISPH) technique to simulate open channel turbulent°ows over a smooth bed. The comparisons indicated that the velocity trend in the upper region is quite promising, but the error becomes larger near the channel bed as the°ow depth becomes shallower.…”
Section: Literature Review On Sph Applications In Open Channel Flowsmentioning
confidence: 99%
“…The comparisons indicated that the velocity trend in the upper region is quite promising, but the error becomes larger near the channel bed as the°ow depth becomes shallower. Kazemi et al [2017] used similar techniques of Fedderico et al [2012] and Tan et al [2015], but with the di®erence that the in°ow particle velocities are linked with those of the inner°uid particles, so that the°ow is evolved naturally without any prescription of the in°ow velocity.…”
Section: Literature Review On Sph Applications In Open Channel Flowsmentioning
confidence: 99%
“…Recently, some pioneering works have been carried out on the treatment of inflow/outflow boundary conditions in SPH, for example, Federico et al , Aristodemo et al and Tan et al . In present study, a similar technique has been adopted but with the difference in that the inflow particle velocities are linked with those of the inner fluid particles, so that the flows are evolved naturally without any prescription of the inflow velocity.…”
Section: Numerical Modelling Schemementioning
confidence: 99%